Markers Of Post-conceptual Painting In Bandung Contemporary Arts (A Case Study On Errata-optika Exhibition - Kiky Rizky Soetisna Putri; Setiawan Sabana (Institut Seni Indonesia Denpasar, 2016)
Painting in its development has undergone various criticisms both of the medium and its conceptual substance. Currently painting is widely regarded as mere representation strategy. This study tries to see and tracing the paradigm shift in the era of contemporary painting, conceptual expansion, particularly the use of optical devices in its creation. Case study in this research is an exhibition in 2007 entitled Errata-Optika that was believed to be an important milestone paradigm shift in contemporary painting. This study used qualitative methods to approach the criticism and the study ofliterature on the history of painting to contemporary era. Observation was carried out as a method of collecting data from the exhibition Errata-Optika. The exhibition featured seven artists and twenty-two paintings that used optical devices in its creation method.Keywords: Post-conceptual Painting, Contemporary Art, Bandung, Exhibition